(3dhGeY GdaUhd aj TQM eHGOF GdCUhds - (3GdgQhj GdCUagGfj, eMeO Jbj Hf MSjf Hf Ydj GdgQhj GdCUagGfj, J (B1299(3g` (B1882(3es
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg GdPj MGQJ HcHQjGA gjHJg ObGFb dWGFa GdChgGe (B... (3Ef Chdi eG jcJSH Hg GdSYGOI GdCHOjI hCYdi eG jUYO Hg GdeYGQL GdYdjI gh GdYde HGdCMcGe GdTQYjIs
(3BNQgG (B:s
(3BNQgG(B: (3fbd GdGJaGb Ydjg (B.. (3WQM GdQhGjI achfgG eNGdaI deG CLeY Ydjg MjK Efg jOd Ydi LhGR GdbVGA dZjQ (B.. (3aJCed Edi efGbH GdYdes
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf, L (B3: 179s
(3GdPQjYI, L (B18: 231s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs